Character creation in neo-realist short stories by V. Vynnychenko (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The analysis of two short stories «Works!» and «Saldatiki» by V. Vinnichenko. The attention is paid to disclosure of the main men's characters and woman' charac-ters. The attempt to analyse the stylistic originality of the author's neorealism was done through the images of the psychological processes of character's internal life and their external displays.
Keywords: neоrealism; creation of the character; character